Vitamin D levels among children, adolescents, adults, and elders in Pakistani population: a cross-sectional study - Saba Arshad; Syed Jaffar Abbas Zaidi (BMC, 2022)
Abstract Background Vitamin D is not only an essential part of a healthy diet but it is also known as the sunshine hormone. It helps to absorb calcium and phosphate within the body and is essential for the development of teeth and bones in growing children. Deficiency in vitamin D causes weak bones, osteoporosis in older individuals, and osteomalacia in children. It also causes loss of alveolar bone around the teeth, increased dental cavities, and other problems associated with gum disease. It can cause depression, fatigue, and appetite loss. This study aims to observe vitamin D deficiency, insufficiency, and sufficiency among children, adults, adolescents, and elders in the Pakistani population. Methods A cross-sectional survey was conducted with 27,880 individuals referred from the general out-patient-department (OPD) to Dow Diagnostic Research and Reference Laboratory (DDRRL) units at Dow University of Health Sciences (DUHS) Karachi, Pakistan, for a period of three months from January to March 2017. They were examined for laboratory findings of serum 25 hydroxyvitamin D levels to determine vitamin D deficiency, insufficiency, and sufficiency among all age groups of both male and female genders. Results A total of 26,750 individuals with a mean age of 38 ± 18 years were statistically examined for laboratory findings of serum vitamin D levels. Vitamin D deficiency was observed in 56% of individuals with a mean log of 1.01 ± 0.18 ng/ml serum vitamin D levels, vitamin D insufficiency in 20% of individuals with a mean log of 1.38 ± 0.05 ng/ml serum vitamin D levels and vitamin D sufficiency in 24% individuals with a mean log of 1.63 ± 0.12 ng/ml serum vitamin D levels. The highest percentage of individuals deficient in vitamin D were children and adolescents of age ranging between 6 to 18 years. Conclusion The findings of vitamin D deficiency in children and adolescents direct higher authorities in the public health sector to take immediate steps to screen, intervene and educate high-risk populations incorporating vitamin D supplements to establish preventive and therapeutic measures.